Longitudinal metabolomics in dried bloodspots yields profiles informing newborn screening for succinic semialdehyde dehydrogenase deficiency. Issue 1 (26th February 2020) - Brown, Madalyn; Turgeon, Coleman; Rinaldo, Piero; Pop, Ana; Salomons, Gajja S.; Roullet, Jean‐Baptiste; Gibson, K. Michael
Abstract: Analyses of 19 amino acids, 38 acylcarnitines, and 3 creatine analogues (https://clir.mayo.edu ) were implemented to test the hypothesis that succinic semialdehyde dehydrogenase deficiency (SSADHD) could be identified in dried bloodspots (DBS) using currently available newborn screening methodology. The study population included 17 post‐newborn SSADHD DBS (age range 0.8‐38 years; median, 8.2 years; 10 M; controls, 129‐353 age‐matched individuals, mixed gender) and 10 newborn SSADHD DBS (including first and second screens from 3 of 7 patients). Low (informative) markers in post‐newborn DBS included C2‐ and C4‐OH carnitines, ornithine, histidine and creatine, with no gender differences. For newborn DBS, informative markers included C2‐, C3‐, C4‐ and C4‐OH carnitines, creatine and ornithine. Of these, only creatine demonstrated a significant change with age, revealing an approximate 4‐fold decrease. We conclude that quantitation of short‐chain acylcarnitines, creatine, and ornithine provides a newborn DBS profile with potential as a first tier screening tool for early detection of SSADHD. This first tier evaluation can be readily verified using a previously described second tier liquid chromatography‐tandem mass spectrometry method for γ‐hydroxybutyric acid in the same DBS. More extensive evaluation of this first/second tier screening approach is needed in a larger population.